PERAN AKSI CEPAT TANGGAP (ACT) INDONESIA DALAM MEMBERIKAN BANTUAN KEPADA ETNIS ROHINGYA DI MYANMAR TAHUN 2017-2019 - Hansyah, Rizki Abibur; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to determine the role of Indonesia's fast-paced action (ACT) in providing assistance to Rohingya ethnic in Myanmar in 2017-2019. During 2017-2019, Rohingya ethnic that remains and living in Burma had experienced a wide range of resettlement and discrimination. As a result they have difficulty in insufficient their needs.This research use the pluralism perspective which believes that states are not the only actors in international world. This research is also guided by theory of transnational activism. The method used is qualitative method. The data collection incorporates interviews and literature study from some journals, books, documents and websites. This research shows that during the year 2017-2019 the Indonesian fast-response action (ACT) has been instrumental in providing assistance to the Rohingya ethnic in Myanmar. Assistance in the form of food aid, drug assistance, residential tent assistance and support assistance. Keyword : Role, ACT,  Rohingya ethnic , ethnic conflict